Desain Interior Ruang Perpustakaan : Perspektif Pengelola Perpustakaan - Bahrul Ulumi (Pustakaloka, 2010)
The stakeholders often unaware that interior design of library will impact on the interest of library user to visit the library. Convenience factor is support by other factors, such as aesthetically and functionally library service. The role of policy makers, librarians, consultants, interior designers and institution leaders must be involved in synergy to create a comfortable library with regard to the principles of libabry interior design.